Risk factors for undernutrition in children under five (6-59) months based on child and parents characteristics - Yuli Hartati; Podojoyo Podojoyo; Nurul Salasa Nilawati; Ahmad Sadiq (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Malnutrition in children under five is influenced by various factors, including child and parent factors. This is because of the different characteristics of each research site.Objective: This study aimed to determine the risk factors for undernutrition in children under five years of age based on the characteristics of the child and parents.Methods: This study used a cross-sectional design with a sample size of 149 children. The sampling was performed using simple random sampling. The research location was the working area of the Taman Bacaan Palembang Community Health Center from May to August 2023. Data were processed bivariately and multivariately using chi-square statistical tests and logistic regression with a confidence level of 95%.Results: The results of the study showed that the risk factors based on child characteristics were birth weight (p= 0,013, OR = 2,778), exclusive breastfeeding (p= 0,024, OR= 2,216), complementary foods (p= 0,002, OR= 2,993), infectious diseases (p= 0,000, OR=10,440), colostrum administration (p= 0,004, Or= 3,682), and immunization (p=0,000, OR= 4,475). Based on parental characteristics, the risk factors for undernutrition were father's education (p= 0,000, OR= 3,907), mother's occupation (p= 0,000, OR= 0,099), family income (p= 0,006, OR= 3,560), and mother's nutritional knowledge (p= 0,000, OR=8,971). The most dominant factors were maternal nutritional knowledge () and maternal education (p=0,000, OR= 20,079).Conclusion: The risk factor for malnutrition in children was immunization (p= 0,000, OR= 14,598) and the characteristics of parents were maternal education (p=0,000, OR= 20,079), with the dominant causal factor being maternal nutritional knowledge.